A Decision Support System based on the DDMCC paradigm for strategic management of capital groups - Twardowski, Zbigniew; Wartini-Twardowska, Jolanta; Stanek-Stanisław (System wspomagania decyzji oparty na paradygmacie DDMCC dla strategicznego zarządzania grupami kapitałowymi, 2011)
The aim of the paper is to present the findings and practical outcomes of research on DSS capable of supporting the consolidations process in management of capital groups.The article presents an original approach to both the design and processing of distributed data acquisition system designed for strategic management, as well as an original approach to the use of such solutions to support strategic decisions for capital groups. The final section of the paper describes the implementation of the financial consolidation support system in capital groups, which is the most recent application of the concept presented
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 206, s. 192-203
Keywords: DSS; capital groups; consolidation process; Data-Dialog-Modeling-Communication-Creativity paradigm; hybrid archicture